Inspired by Calvin Lin: Any part 1

Geometry Level 4

Suppose A D , B E , C F AD, BE, CF are the medians of a triangle A B C ABC , with side B C = 10 BC = 10 , intersecting at G G .

In the quadrilateral A E G F AEGF , suppose A E × A F = 3 × G E × G F AE\times AF = 3\times GE\times GF ,
evaluate A B × B E + A C × C F A D \dfrac{AB\times BE+ AC\times CF}{AD} .


Inspired by Calvin's recent median potpourri!
Do solve the next part .


The answer is 20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Aditya Kumar
Dec 29, 2014

Here is the solution: A E × A F = 3 × G E × G F AE\times AF = 3\times GE\times GF

2 A E × 2 A F = 6 × G E × 2 G F \implies 2AE\times 2AF = 6\times GE\times 2GF

A C × A B = 6 × G E × G C \implies AC \times AB = 6\times GE\times GC ...(1)

But we know that the medians divide a triangle into six e q u a l equal smaller triangles. So,

A r e a o f Δ A B C = 6 × A r e a o f Δ G E C Area of \Delta ABC = 6\times Area of \Delta GEC

A C × A B × sin ( A ) = 6 × G E × G C × sin ( E G C ) \implies AC\times AB\times \sin(\angle A) = 6\times GE\times GC\times \sin(\angle EGC)

Using (1), sin ( A ) = sin ( E G C ) \implies \sin(\angle A) = \sin(\angle EGC)

A = E G C \implies \angle A = \angle EGC (** justification for this step: at last)

This makes quadrilateral A E G F AEGF cyclic. Applying Ptolemy's theorem,

A E × G F + A F × G E = A G × E F AE\times GF + AF\times GE = AG \times EF

2 A E × 3 G F + 2 A F × 3 G E = 2 × 3 2 × A G × 2 E F \implies 2AE\times 3GF + 2AF\times 3GE = 2\times \frac{3}{2}\times AG \times 2EF

A C × C F + A B × B E = 2 × A D × B C \implies AC\times CF + AB\times BE = 2\times AD \times BC

\implies the answer is 2 × B C = 20. 2\times BC = 20.

Pending justification: If 180 A = E G C 180 - \angle A = \angle EGC , this would mean:

A = E G F = B G C \angle A = \angle EGF = \angle BGC ,

That is B C BC subtends equal angles at A A as well as at G G \implies G G lies on the circumcircle i.e. outside of the triangle (since only the vertices of a triangle are the triangle's points on this circle, the other points of the circle are necessarily outside)

But this is impossible: Think of the centroid's role as the centre of mass, hundreds of other reasonings!

Brilliant solution! Only I could not get the part that is 'Pending justification'.

Why do you say 180 A = E G C 180- \angle A = \angle EGC when actually A = E G C \angle A = \angle EGC ?

Ujjwal Rane - 6 years, 2 months ago

Log in to reply

I cannot be more apologetic for such a terribly delayed response! Actually, sin A = sin E G C \sin\angle A=\sin\angle EGC does not mean A = E G C \angle A = \angle EGC . It can also happen when A = 180 E G C \angle A = 180 -\angle EGC . So I justify at the end that this second case is not true, the two angle have to be equal and not supplementary.

Aditya Kumar - 5 years, 5 months ago
Mark Hennings
Sep 18, 2016

Let the medians at A , B , C A,B,C have lengths m a , m b , m c m_a,m_b,m_c . Then Apollonius' Theorem tells us that m a = 1 2 2 b 2 + 2 c 2 a 2 m_a \; = \; \tfrac12\sqrt{2b^2 + 2c^2 - a^2} and similarly for m b , m c m_b,m_c . The condition A E × A F = 3 G E × G F AE \times AF = 3 GE \times GF can be read as 1 2 b × 1 2 c = 3 × 1 3 m b × 1 3 m c m b m c = 3 4 b c ( 2 a 2 + 2 c 2 b 2 ) ( 2 a 2 + 2 b 2 c 2 ) = 3 b c \begin{array}{rcl} \tfrac12b \times \tfrac12c & = & 3 \times \tfrac13m_b \times \tfrac13m_c \\ m_bm_c & = & \tfrac34bc \\ \sqrt{(2a^2 + 2c^2 - b^2)(2a^2 + 2b^2 - c^2)} & = & 3bc \end{array} Squaring and simplifying, we obtain ( a 2 + b 2 + c 2 ) ( 2 a 2 b 2 c 2 ) = 0 (a^2 + b^2 + c^2)(2a^2 - b^2 - c^2) \; = \; 0 so that b 2 + c 2 = 2 a 2 b^2 + c^2 = 2a^2 , and therefore m a = 3 2 a m_a = \tfrac{\sqrt{3}}{2}a .

Now ( A B × B E + A C × C F ) 2 = ( c m b + b m c ) 2 = c 2 m b 2 + 2 b c m b m c + b 2 m c 2 = 1 4 c 2 ( 2 a 2 + 2 c 2 b 2 ) + 3 2 b 2 c 2 + 1 4 b 2 ( 2 a 2 + 2 b 2 c 2 ) = 1 2 ( a 2 + b 2 + c 2 ) ( b 2 + c 2 ) = 3 a 4 \begin{array}{rcl} (AB \times BE + AC \times CF)^2 & = & (cm_b + bm_c)^2 \; = \; c^2m_b^2 + 2bcm_bm_c + b^2m_c^2 \\ & = & \tfrac14c^2(2a^2 + 2c^2 - b^2) + \tfrac32b^2c^2 + \tfrac14b^2(2a^2 + 2b^2 - c^2) \\ & = & \tfrac12(a^2+b^2+c^2)(b^2+c^2) \; = \; 3a^4 \end{array} Thus A B × B E + A C × C F A D = 3 a 2 m a = 2 a = 20 \frac{AB \times BE + AC \times CF}{AD} \; = \; \frac{\sqrt{3}a^2}{m_a} \; = \; 2a \; = \; \boxed{20} It is worth noting that the triangle can be equilateral, with a = b = c = 10 a=b=c=10 and m a = m b = m c = 5 3 m_a = m_b = m_c = 5\sqrt{3} .

Nice solution.

Ayush Pattnayak - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...